If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(8 + 7a) = -23 (8 * -5 + 7a * -5) = -23 (-40 + -35a) = -23 Solving -40 + -35a = -23 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -35a = -23 + 40 Combine like terms: -40 + 40 = 0 0 + -35a = -23 + 40 -35a = -23 + 40 Combine like terms: -23 + 40 = 17 -35a = 17 Divide each side by '-35'. a = -0.4857142857 Simplifying a = -0.4857142857
| (^3√17y^2)/(^3√12x) | | 4x^2-25z^2+7z=-12 | | 12/2x/5/6x | | -22=-5+7(x-9) | | 7r^2+46r=21 | | (ln(7)-ln(1))/6 | | m-2m-3m-3= | | 8=x?2 | | (x-4)(7x+2)=0 | | y=y/7 | | -10v+2=-7 | | 8p^2=-26p-6 | | x^2-15= | | 8x^3-2x^2-27x+18=0 | | 3p-11=8p-21 | | -30=32c-24 | | 2x^2+4x-60=6x | | 7x-2y=-24 | | 6n/3n | | 7x-2y=-27 | | 20x-8=16x | | 3a+2b=-5 | | 3x^2+3x-60=6x | | 3v+8=17 | | a+4b=5 | | (9x-19)-8=14x | | 3a+2b=13 | | 5t-2x+3t= | | 5a+4b=23 | | -6(1-4s)=35 | | 19=4n+5n | | tg(2x+30)=-1 |